Pelatihan Manajemen Pemasaran dan Diversifikasi Produk sebagai Solusi Peningkatan Daya Saing Petani di Tengah Risiko Gagal Panen: Indonesia - Krisnanda, Krisnanda; Widyastuti, Winda; Nadia, Linda Putri (UII, 2026)
ABSTRACT This community service program aims to enhance the competitiveness of farmer groups in Gajah District, Demak Regency through training in marketing management, product diversification, and crop failure risk management using the Agricultural Insurance Scheme (Asuransi Usaha Tani Padi, AUTP). The program was motivated by farmers’ limited ability to market their products effectively, lack of product innovation, and insufficient understanding of agricultural risk protection instruments. A participatory approach was employed, including field observations, focus group discussions, practical training, and pre and post tests to assess knowledge improvement. The program emphasized three key aspects: strengthening digital marketing capacity, developing value added agricultural products, and providing socialization on AUTP as a crop failure mitigation tool. The results showed significant improvements in farmers’ understanding of digital marketing and product diversification, along with greater awareness of agricultural insurance benefits. This initiative successfully strengthened farmers’ economic resilience, farming sustainability, and preparedness against climate-related production uncertainties. Therefore, the integration of marketing management training, product diversification, and AUTP implementation serves as an effective strategy to enhance farmers’ long term competitiveness.